Exploring the Differences between the Selected forms of Apprenticeship and Indigenous Igbo Business Mentoring - Dare Ojo OMONIJO; Michael C. ANYAEGBUNAM; Chiamaka Ogechukwu JOE-AKUNNE; Edith AWOGU-MADUAGWU; Jonathan Adedayo ODUKOYA (Communications of International Proceedings, 2020)
Previous studies have shown several traditional apprenticeships in different vocations or occupations. These include dying, pottery, the weaving of cloth and hairdressing known as “onidiri” in Yoruba land, southwest Nigeria etc. Previous studies have shown that most of these occupations are in existence in other geopolitical zones of Nigeria except the indigenous Igbo business mentoring which is strictly restricted to Southeast Nigeria. Although, most of these apprenticeships are meant for skill impartation, spite of that it appears that indigenous Igbo business mentoring is unique in certain areas which are yet to be fully illustrated in academic and business literature in Nigeria. The present study intends to address this flaw in knowledge. It engages data from the secondary source which means, materials from the library and internet were used to collect information for the study while it considers content analysis as the most appropriate methodology due to its nature. The paper argues in the concluding section that the selected forms of apprenticeship share a common boundary with indigenous Igbo business mentoring but strictly different in areas of the financial assistance known as “idu-odibo” available for the youth who engaged in the scheme (“igba-odibo”) but such an opportunity is not in existence in other apprenticeships. Where payment is concerned in other apprenticeships, it involves apprentices paying for the skills learnt and certificates to be issued for practice. The idea of masters or mentors offering financial assistance to the apprentices for a start-up makes the indigenous Igbo business mentoring a unique one.
Keywords: Differences; selected forms of Apprenticeship; indigenous Igbo Business Mentoring.